Colonial legacy and traps in the social-ecological systems of forest management - C.D.A. Depari (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The persistence of colonial controls in present-day forest management has long been recognized as a potential threat to the resilience of social-ecological systems. These controls have created barriers that disconnect individuals from their land and diminish the forest diversity. In Mount Merapi, this maladaptation is manifested through the long-tailed macaque’s invasion of farmlands, triggered by the state’s failure to reforest the targeted 480 ha of damaged land after the 2010 eruption. This study aims to qualitatively interrogate factors that are hindering the swift restoration of Mount Merapi's social-ecological systems. This will be achieved by investigating the intricate dynamics of the area over various time frames, utilizing the panarchy framework developed by Holling and Gunderson. The framework is well-known for its capacity to facilitate a holistic understanding of social-ecological systems but is also intrinsically ambiguous to capture the complexity. The study’s novelty lies in its adoption of Boyer’s refined panarchy models and Boonstra and De Boer’s systematic analysis to address the methodological concern toward a better understanding of social-ecological systems.METHODS: This study utilizes various techniques for data collection, including semi-structured interviews, literature reviews, and field observations. The interviews involved informants who were selected through purposive sampling and focused on exploring Boyer's panarchy characteristics. In order to ensure the reliability of the data, triangulation was conducted prior to the development of panarchy models.FINDINGS: The findings indicate that the strict forest controls embedded in the state’s forest management since the colonial periods had created rigidity and poverty traps. The concept of the rigidity trap pertains to a reforestation strategy that utilized laborers and territories for ecological conservation, restricted local communities from utilizing forests, and diminished biodiversity by favoring the introduction of non-native Acacia decurrens.CONCLUSION: To address traps, this study recommends the need to use a panarchy approach that facilitates a comprehensive understanding of social-ecological systems and to transfer governance to local people which must be based on an in-depth understanding of the local history, knowledge, and cultures.